Analisis Yuridis Hukuman Mati Terhadap Pelaku Korupsi Dana Covid-19 Dalam Perpektif HAM - Ramadhani, Sri Ridma; Aufa, Muhammad Fikri; Utami, Mieke Aprilia; Alamudi, Ichwan Ahnaz; Erliani, Sri (Jayapangus Press, 2025)
Every action taken by humans will always have consequences. If the action taken is a bad action and has an impact on others, then this action will result in sanctions. This results in the need for clear rules made by the government in a country, in order to create harmony in society in the nation and state. Indonesia, although it allows the death penalty for perpetrators of crimes stated in Article 11 of the Criminal Code, including corruption, in fact the death penalty is very rarely carried out in Indonesia, one of the reasons for the rare death penalty is that people still think about human rights. This study aims to analyze the death penalty for perpetrators of corruption of the Covid-19 pandemic funds in terms of human rights. This research is a juridical-normative type of research, namely legal research conducted by the method of reviewing library materials. Giving the death penalty to corruptors is very appropriate because it can be used as shock therapy because psychologically corruptors who are sentenced can be used as an example to influence other parties not to commit corruption. The results of the study revealed a discrepancy between the harsh legal basis and the commitment to human rights principles in the Indonesian legal system. In addition, the failure to apply the death penalty to corruptors of pandemic funds was influenced by various factors, such as the direction of legal policy taken by the government, pressure from the international community, and the low integrity of law enforcement officers. This study concludes that the threat of the death penalty has not been able to function effectively as a deterrent because it is not accompanied by consistent law enforcement. Therefore, this study contributes to the discourse on reforming corruption criminalization policies by emphasizing the need for a balance between the values ​​of justice, humanity, and legal effectiveness.